PECULIARITIES OF CYTOKINES AND THEIR PROGNOSTIC VALUE IN PATIENTS WITH CHRONIC GLOMERULONEPHRITIS - M. Kolesnyk; V. Driyanska; M. Velichko; G. Drannik; V. Savchenko (Ukrainian Journal of Nephrology and Dialysis, 2017)
Introduction. Cytokines are important to take part in immunogenesis and progression of glomerulonephritis (GN), therefore the analysis of these indices in dependence of type of GN forms as prognosys results of treatment.Aim of the work is to determine the peculiarities of pro-inflammatory cytokines (TNFα, MCP-1, IL-17, -18, -23) and anti-inflammatory TGF- β1 and their association with form GN with nephritic syndrome (NS) and possibility use cytokines as prognostic markers.Materials and methods. Using IFA, the level of the above mentioned cytokines was studied in the blood serum of 117 patients with proliferative (33) and non-proliferative (84) CGN, NS forms. There was also analyzed the changes of these indices in the patients with subsequent clinical laboratory remission (59) and patients without one (58).Results. The GN, NS patients showed statistically higher level of the pro- inflammatory cytokines – TNFα, MCP-1, IL-17 (with more high indices last one in the proliferative forms of GN, and IL-17 in nonsensitive to immunotherapy patients). High level profibrogenic TGFβ, and the ratio TNFα /TGFβ reflect the prevalence of anti-inflammatory reactions and high activity of monocytes - macrophages and T-helpers17. The positive effect of the treatment associates with the statistically decreased TNFα, MCP-1 and TGFβ1 levels in the patients with proliferative forms GN; the TGFβ1 - for patients with non-proliferative GN forms.Conclusion. The changes cytokine profiles may be use as predictors of results the immunosuppressive therapy.